Equity research - paypal holdings, Inc - Malinauskaite, Giedre (2021)
This paper is done to value PayPal Holdings ($PYPL) for an investment of a 12 month time horizon from a fundamental analysis perspective, utilizing various methods such as discounted cash flow analysis and multiple analysis. By seeking a fair valuation, weintend to reach a conclusion regarding the return expectations for an investor by holding Paypal for the incoming 12 month period, considering the future growth potential as well as risks and uncertainties.